REORGANIZAÇÃO DA PROPRIEDADE FUNDIÁRIA, REFORMA AGRÁRIA E A LUTA DO MST PELA DEMOCRATIZAÇÃO DA TERRA NO BRASIL (Revista Paradigma, 2022)
This work carries out a study of the theme “Land Reorganization to Combat Inequality - Agrarian Reform and the Struggle for Democratization of the Land in Brazil”. The discussion is guided by the problem of the Brazilian Latifundium, where the Agrarian Reform Policy appears as the main policy to combat inequality. In the course of the discussion, several philosophical conceptions of property are approached through a bibliographical confrontation, until reaching contemporary property in Brazil and its social function, in order to carry out an analysis by the hypothetical deductive method about the right to agrarian property and to point out that Landless Workers Movement (MST) in the struggle for land democratization in Brazil.